Konseling Individual Pendekatan Behavioral Teknik Behavior Contract dalam Mengatasi Rendahnya Kemandirian Belajar - ningsih, caci mustika; supriyo, supriyo; mugiarso, heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research was conducted based on the phenomenon in Muhammadiyah orphanage Semarang which shows a low level of self learning. This research aimed to determine changes of children’s self learning inMuhammadiyah orphanage Semarang through individual counselin with behavioral approach, behavior contract technique. This research uses a case study approach that is directed into the handling of the case. The focus of this research is the low level of children’s self learning when the children in the orphanages. Data collection methods used wereinterviews, observation, and documentation. The data’s validity testing technique is by triangulation. Analysis of the data used analysis of content, comparative and logic. The subjects of research are AW, EDP, and MKG that have problems with low level of self learning. Theresults of the counseling research to three children is known that the children’s self learning when in the orphanage is already increase, so based on the results of the research can be concludedthat the lack of counselee’s self learning can be solved through individual counseling with behavioral approach, behavior contract technique.